Juízo de admissibilidade do recurso extraordinário à luz do entendimento doutrinário e jurisprudencial - Nagildo, Eduarda Fronza (My University, 2024)
The Extraordinary Appeal, a type of appeal to be analyzed in the Federal Supreme Court, as well as other appeals, is subject to the analysis of compliance with certain procedural and material requirements so that it can effectively have its merits analyzed, this analysis is called admissibility judgment, object of of the present monograph. Since the extraordinary appeal is one of the only appeals that can be analyzed by the STF, the "last instance" of appeal, of course, its admission hypotheses are quite specific and, therefore, the central objective of this research is to carry out a doctrinal and jurisprudential analysis interpretation of the legal provisions that deal with admissibility and thus provide an overview of the main aspects related to the subject. Therefore, it is proposed to objectively verify the necessary requirements, the understanding established by the court through the precedents and the doctrinal interpretation of aspects involving the admissibility of the appeal. [resumo fornecido pelo autor]
O Recurso Extraordinário, espécie recursal a ser analisada no Supremo Tribunal Federal, assim como outros recursos, está sujeito à análise do cumprimento de determinados requisitos processuais e materiais para que possa efetivamente ter o seu mérito analisado, análise esta chamada de juízo de admissibilidade, objeto da presente monografia. Sendo o recurso extraordinário um dos únicos recursos passíveis de serem analisados pelo STF, a "última instância" recursal, por certo que as suas hipóteses de admissão são bastante específicas e, portanto, o objetivo central da presente pesquisa é realizar uma análise doutrinária e jurisprudencial da interpretação dos dispositivos legais que tratam da admissibilidade e assim realizar um panorama dos principais aspectos atinentes ao tema. Propõe-se, assim, a verificar de forma objetiva quais os requisitos necessários, o entendimento sedimentado pelo Tribunal através das súmulas e a interpretação doutrinária a aspectos que envolvem a admissibilidade do recurso. [resumo fornecido pelo autor]
Keywords: Processo civil; Recursos (Direito); Recurso extraordinário; Brasil. Supremo Tribunal Federal